SERANGAN HAMA Cylas formicarius F. (coleoptera : curculionidae) PADA BEBERAPA SENTRA TANAMAN UBI JALAR ( Ipomoea batatas L.) DI KABUPATEN MINAHASA SELATAN, MINAHASA, DAN KOTA TOMOHON - Edi . Handoko; Odi R. Pinontoan; James B. Kaligis; Henny V.G. Makal (COCOS, 2013)
ABSTRACTPlant sweet potato (Ipomoea batatas. L) is one of the crops that have a high nutrient, sweet potato ranks ninth among food crop in the world. This study aims to determine the percentage of the pest in some centers C.formicarius sweet potato plant, in the district of South Minahasa, Minahasa regency, and Tomohon. The benefits of this research are expected to provide information on the percentage of C.formicarius pests, so it can be used as an input in the preparation of control programs in the future. results showed that the percentage of pests C. formicarius highest in South Minahasa Regency Village District Sinisir Modoinding 36.09% at follow Tomohon Tomohon western sub Desa Woloan 10.06% and Minahasa Regency Village District Sumarayar North Langowan 8.78%. high percentage pests C. formicarius in South Minahasa Regency Village Sinisir Modoinding district because of the availability of food but to attack yams C. formicarius also attack potato plants so that pest populations C. formicarius Sinisir village increased.Keywords: Sweet potato (Ipomoea batatas), Attack Cylas formicarius F. (Coleoptera curculionidae),